Dietary intake of pregnant women and their infants in a poor black South African community - D Mostert; NP Steyn (AOSIS, 2005)
The aims of this study were (i) to determine the dietary intake of women in a poor rural area during pregnancy and lactation, and (ii) to determine the nutritional status and dietary intake of their infants at age 6 months. We recruited 46 women, below 40 years old, in their 2nd trimester of pregnancy. The subjects were living in a rural area of Limpopo Province. Their heights and weights were recorded, as were their diets during pregnancy and for the first 6 months after delivery. We also recorded weights, lengths, and dietary intake of the infants at 3 and 6 months after birth. The subjects were living in severe poverty: none had running water and almost all did their cooking over an open fire. None of the subjects smoked and only one consumed alcohol. The diets of the subjects consisted mainly of maize, brown bread, sweetened beverages (cold drink and tea), and small amounts of vegetables and chicken. The diets were adequate in protein but were marginal in energy and in dietary fibre, and may be deficient in numerous micronutrients, particularly calcium, iron, zinc, niacin, folate, and vitamins A, C, E, and B6. This was seen during pregnancy and lactation. Blood analysis 6 months after birth revealed normal levels of vitamins A and E and an absence of anaemia. Body mass index (BMI) of the women was 23.9 } 5.3 kg/m2 (mean } SD) when measured 6 months after birth. Those above 25 years old had a higher BMI than did younger subjects (25.5 vs. 22.2; p= 0.028). Overall, 24% were overweight (BMI 25-30) while 9% were obese (BMI > 30). Most infants (93%) were breastfed for at least 6 months but exclusive breastfeeding was only done by 65% of mothers. One-third of breastfed infants also received formula. The use of formula while breastfeeding was twice as common among mothers aged above 25 years (46% vs. 23%). Early introduction of solid foods was very common in this group. Younger mothers introduced solids in the first month (51%) more often compared with older mothers who tended to introduce solids at 2-3 months (64%). The most common solid food given was maize meal porridge (by 78% of all mothers). Mean BMI was low at birth (< 15), but this reached a normal value by 6 months. A significant fraction of the infants was underweight or short (i.e., stunted), based on being below the 3rd percentile compared with NCHS standards. Underweight was seen in 15% at birth, falling to 10% at 6 months, whereas 15% had a short length at birth, rising to 35% at 6 months. Underweight tended to be more common in boys and short length in girls. This study found that pregnant and lactating women had diets low in energy and micronutrients as reflected by the high prevalence of underweight at birth. Most infants were exclusively breastfed, but the benefit of this was offset by the early introduction of solid foods having a low energy and nutrient density. By 6 months, the prevalence of stunting had more than doubled.